2017
DOI: 10.2147/jir.s130974
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular matrix of eggshell displays anti-inflammatory activities through NF-κB in LPS-triggered human immune cells

Abstract: Avian eggshell membrane (ESM) is a natural biomaterial that has been used as an alternative natural bandage on burned and cut skin injuries for >400 years in Asian countries, and is available in large quantities from egg industries. Our aim was to characterize ESM that was separated and processed from egg waste, and to study whether this material possesses anti-inflammatory properties, making it suitable as an ingredient in industrial production of low cost wound healing products. Our results show that the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 60 publications
2
34
0
8
Order By: Relevance
“…Processed eggshell membrane powder (PEP) used in this study was prepared as previously described [ 16 ]. PEP was sterilized by gamma irradiation at 25 kGy before in vitro (cell culture) and in vivo (murine wound model) studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Processed eggshell membrane powder (PEP) used in this study was prepared as previously described [ 16 ]. PEP was sterilized by gamma irradiation at 25 kGy before in vitro (cell culture) and in vivo (murine wound model) studies.…”
Section: Methodsmentioning
confidence: 99%
“…The eggshell membranes are a functional equivalent of ECM, which surrounds the egg white and serves both protective and supportive roles during eggshell mineralization [ 12 ]. Its composition and structural features have been highly characterized [ 13 ]; the meshwork of fibers is approximately 90% proteinaceous [ 14 ], and also contains complex carbohydrates such as glycosaminoglycans (GAGs) [ 15 ] and N-glycans [ 16 ]. Structural proteins such as cysteine-rich eggshell membrane proteins (CREMPS) and collagens (particularly type X) are abundant constituents, together with glycoproteins, Ca-regulatory proteins and enzymes with a disintegrin-like and metalloproteinase domain with thrombospondin type 1 motif (ADAMs) [ 13 , 17 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that scaffolds can be used to release proper doses of drugs that depend on cytotoxicity of silver nanoparticles (AgNPs) 240. Vuong et al 241. reported that processed ESM powder and its soluble carbohydrate components exhibit anti‐inflammatory and immune modulator properties in monocytes and macrophages.…”
Section: Second Generation Agricultural Wastes and Their Usesmentioning
confidence: 99%
“…27 Egg shell membranes or egg shell membrane powder have been used as natural bandage for burns and injuries in traditional Asian medicine. Egg shell membrane powder and its carbohydrate constituents have been recently been demonstrated to exert anti-inflammatory effects 119,120 supporting their effectiveness.…”
Section: Yolk As Source Of Antibodiesmentioning
confidence: 99%